The real mound builders of North America : a critical realist prehistory of the Eastern Woodlands, 200 BC-1450 AD - Byers, A. Martin, 1937- (Lexington Books, 2018)
"The Real Mound Builders of North America contrasts the dominant evolutionary view that emphasizes abrupt discontinuities with the Hopewellian ceremonial assemblage and mounds. Byers argues that these communities persisted unchanged in terms of their essential social structures and cultural traditions, varying only in terms of ceremonial practices that manifested these deep structures. This continuist historical trajectory view stands in contrast to the current dominant evolutionary view that emphasizes abrupt social and cultural discontinuities with the Hopewellian ceremonial assemblage and earthworks, mounds and embankments."--